2020
DOI: 10.1080/19359705.2020.1843582
|View full text |Cite
|
Sign up to set email alerts
|

Emotional abuse among Lesbian Italian women: Relationship consequences, help-seeking and disclosure behaviors

Abstract: Objective: The study aims to provide a preliminary examination of the psychometric properties of the Italian version of Multidimensional Measure of Emotional Abuse (MMEA) and aims to investigate consequences of emotional abuse for the relationship, help-seeking and disclosure behaviors, among a sample of lesbian women. Methods and participants: One hundred and sixty-five lesbian volunteers filled in a self-report questionnaire including a measure of emotional abuse (MMEA) investigating the consequences of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 90 publications
0
16
0
9
Order By: Relevance
“…All the seven studies surveying informal sources and providing quantitative data found friends and family (i.e., parents, relatives, or siblings) to be in the top three sources participants turned to when they sought help. Friends, in particular, were listed as the most common contacted source in six (Renzetti, 1989;Merrill & Wolfe, 2000;McClennen et al, 2002;Sylaska & Edwards, 2015;Ngo, 2018;Battista et al, 2020) out of seven of these, ranging from 25% (Sylaska & Edwards, 2015) to 85% (Merrill & Wolfe, 2000). The studies providing qualitative descriptions (Irwin, 2006;Donovan & Hester, 2011;Hardesty et al, 2011;Guadalupe-Diaz, 2013;Oliffe et al, 2014;Freeland et al, 2018) corroborated this aspect as well: among participants who sought help, turning to informal sources was often the most common choice.…”
Section: Help-seeking Modesmentioning
confidence: 86%
See 4 more Smart Citations
“…All the seven studies surveying informal sources and providing quantitative data found friends and family (i.e., parents, relatives, or siblings) to be in the top three sources participants turned to when they sought help. Friends, in particular, were listed as the most common contacted source in six (Renzetti, 1989;Merrill & Wolfe, 2000;McClennen et al, 2002;Sylaska & Edwards, 2015;Ngo, 2018;Battista et al, 2020) out of seven of these, ranging from 25% (Sylaska & Edwards, 2015) to 85% (Merrill & Wolfe, 2000). The studies providing qualitative descriptions (Irwin, 2006;Donovan & Hester, 2011;Hardesty et al, 2011;Guadalupe-Diaz, 2013;Oliffe et al, 2014;Freeland et al, 2018) corroborated this aspect as well: among participants who sought help, turning to informal sources was often the most common choice.…”
Section: Help-seeking Modesmentioning
confidence: 86%
“…While marginalization is taken into consideration as a barrier (Grigsby & Hartman, 1997), its conceptualization is single-layered, and does not account for possible (Scherzer, 1998;Merrill & Wolfe, 2000;McClennen et al, 2002;St. Pierre & Senn, 2010;Sylaska & Edwards, 2015;Rausch, 2016;Battista et al, 2020) Semi-structured interviews 5 (Hardesty et al, 2011;Walters, 2011;McDonald, 2012;Oliffe et al, 2014;Bloom et al, 2015) Multi-method approaches 4 (Renzetti, 1989 (surveys, unstructured Renzetti, 1992) 63 gay men, self-identified as victims of SSIPV HSM: Description of use of formal and informal sources along with perceived helpfulness (data available). Most contacted sources: friends (65%), relatives (56%), psychiatrist (52%), psychologist (51%).…”
Section: Barriers To Help-seekingmentioning
confidence: 99%
See 3 more Smart Citations